Nuclear receptor 4A1 is critical for neutrophil-dependent pulmonary immunity to Klebsiella pneumoniae infection - Sugitani, Norie; Henkel, Matthew; Partyka, Jessica; Applegate, Alexander; Kemp, Felicia; Byersdorfer, Craig A.; Eddens, Taylor; Campfield, Brian T. (Frontiers in Immunology, 2025)
IntroductionBacterial pneumonia is a burdensome, costly disease and increasingly challenging to treat due to antibiotic resistance. Complex host-pathogen interactions regulate protective immunity. Neutrophils play a central role in pulmonary bacterial immunity, and mechanistic understanding of neutrophil functions in bacterial pneumonia has potential clinical and fundamental application. Nuclear receptor 4a1 (Nr4a1), a member of the nuclear orphan receptor family, has been described to regulate inflammation and immune development in a cell type-specific manner, but its role in pulmonary host defense is not well understood.MethodsWild-type (WT) and Nr4a1-/- mice, as well as bone marrow chimeric and Gr-1+ antibody depleted mice, were infected with Klebsiella pneumoniae and assessed for bacterial burden in the lung and spleen, gene transcription, protein levels, histology and cellular abundance by flow cytometry in the lung. WT and Nr4a1-/- neutrophils were exposed to live Klebsiella pneumoniae to quantify bacterial killing, as well as bulk RNA sequencing to assess transcriptomic differences.ResultsNr4a1-deficient mice are highly susceptible to Klebsiella pneumoniae pneumonia, which was mediated by Nr4a1 expression in immune cells. Gr-1+ antibody depletion ameliorated the Nr4a1-dependent phenotype. Ex vivo, Nr4a1-deficient neutrophils had impaired bactericidal capacity, and transcriptomic analysis identified an Nr4a1-dependent host defense program in neutrophils.DiscussionNeutrophil Nr4a1 expression is critical for defense against K. pneumoniae infection by regulating the neutrophil transcriptome. These findings suggest targeting Nr4a1 signaling pathways in neutrophils may be useful for bacterial pneumonia treatment.